One year effectiveness of neuromuscular exercise compared with instruction in analgesic use on knee function in patients with early knee osteoarthritis: the EXERPHARMA randomized trial. Issue 1 (January 2018) - Holsgaard-Larsen, A.; Christensen, R.; Clausen, B.; Søndergaard, J.; Andriacchi, T.P.; Roos, E.M.
Summary: Objective: To test long-term effectiveness of neuromuscular exercise (NEMEX) with instructions in optimized pharmacological treatment (PHARMA) on activities of daily living (ADL) in patients with early knee osteoarthritis. Design: 12-months follow-up from a randomized controlled trial. Participants with mild-to-moderate medial tibiofemoral knee osteoarthritis were randomly allocated to 8 weeks NEMEX or PHARMA. The primary outcome measure was the ADL-subscale of the Knee Injury and Osteoarthritis Outcome Score (KOOS). Secondary outcome measures included the other four KOOS-subscales, the University of California Activity Score (UCLA) and the European Quality of Life-5 Dimensions. Results: Ninety-three patients (57% women, 58 ± 8 years, body mass index 27 ± 4 kg/m 2 ) were randomized to NEMEX ( n  = 47) or PHARMA group ( n  = 46) with data from 85% being available at 12-months follow-up. Good compliance was achieved for 49% of the participants in NEMEX (≥12 sessions) and 7% in PHARMA (half the daily dose of acetaminophen/NSAIDs ≥ 28 days). Within-group improvements in NEMEX were considered to be clinically relevant (≥10 points) for all KOOS-subscales, except Sport/Rec whereas, no between-groups difference in the primary outcome KOOS ADL (3.6 [−2.1 to 9.2]; P  =  0.216 ) was observed. For KOOS Symptoms, a statistically significant difference of 7.6 points (2.6–12.7; P  =  0.004 ) was observed in favor of NEMEX with 47% improving ≥10 points. Conclusions: No difference in improvement in difficulty with ADL was observed. NEMEX improved knee symptoms to a greater extent with half of patients reporting clinically relevant improvements. ClinicalTrials.gov Identifier: NCT01638962 (July 3, 2012). Ethical committee: S-20110153